Contratransferência: um dispositivo clínico psicanalítico - Dias, Helena Maria Melo (2007)
As we were touched by the Sarah case, a scrutiny was performed about the concept of Countertransference which was framed by authors whom highlighted its relevance throughout a psychoanalytical treatment. Among them, we regard Pierre Fédida as the one who amplified and brought the matter into a deeper understanding, as he considered the Metapsychology within the psychological processes of the therapist upon the psychoanalysis technique. The articulations of the case in question, allied with such thought, are the cornerstones of this thesis which understands Countertransference as an inherent mechanism to the analytical scenario and thus, adequate as prescribed therapy. Therefore, a specific comprehension was sought about this technique developed by Freud which has dreaming as its basic paradigm. A thought was also given about its methodology by Ferenczi, based upon cases which were reckoned to be difficult to deal with and aliens to his own arena, fact which provoked increasing scientific publications on the topic of countertransferencial effects in the analysis. The major characteristic of this research has its core on the topic of the first objectional relationships in a baby s psychological constitution which turns to be the transferencial basis upon which the therapist intervene in a patient s psychism. From this perspective, Fédida supported the inherent model of countertransference as a fictional relationship, mother-son-like, capable of becoming both resonant and contigent to a patient s state of anguish and hence proper to the treatment. In the Sarah case the Countertransference s Auto-Transgression, a critical scenario during the analysis, permited the patient to both metabolize and metaphorize his psycologhical suffering